Financial Business Analysis of Semi Modern Chicken Broiler House (Case Study on UD. Giri Sari Denpasar Timur) - I W., Susana; Sukanata, I W.; Suparta, I N. (Jurnal Peternakan Tropika; Vol 6 No 3 (2018), 2018)
The chicken slaughtering business is about processing broiler chickens into carcass that would then be marketed to consumers. This study aims to determine operational management, finansial feasibility, as well as the sensitivity of the feasibility of semi modern chicken slaughterhouse business at UD. Giri Sari. This research was carried out at UD Chicken Slaughterhouse. Giri Sari Denpasar, Desa Penatih Dangin Puri, Kecamatan Denpasar Timur Denpasar Regency for 1 month from April to May 2018. The data used are primary data and secondary data. The variables used in this study are operational management chicken slaughterhouse and financial feasibility analysis. Financial feasibility is determined based on the results of the Net Present Value analysis, Internal Rate of Return, Net Benefit Cost Ratio, Pay Back Period, Break Even Point, and sensitivity analysis. The results showed that this business generated NPV 15.025.348.898,76, IRR 101,94%, Net B / C 5,06, PBP 3 months 20 days (0,30 years) and BEP 6 years. The results of the sensitivity analysis show that this business is less sensitive to the increase in the price of live chickens by 14,52% and is very sensitive to the decline in carcass prices by 3,39%. Therefore the business of Chicken Slaughterhouse UD. Giri Sari Denpasar is financially feasible. Although this business is feasible to run, it is necessary to pay attention to cutting management so that the quality of the carcass is in accordance with SNI in the RPA.  Keywords: The chicken slaughtering business, carcass, financial analysis